Big Data Analysis of Covid-19 Spread Based on Distribution Map and Protocol Regulations with Business Intelligence - Anita Sindar Sinaga; Arjon Samuel Sitio (CCIT Journal, 2022)
Various parties analyze the total cases of the Corona virus every day to prevent a high level of spread. Big Data technology involves data that is diverse, rapidly changing, super large in size so that conventional technology cannot be handled effectively. Four stages of processing Big Data until the output it produces is information for users, namely acquired, accessed, analytics, and application. Business Intelligence serves to transform operational, transactional data into useful information within the company. Big Data Analytics analyzes information, IDE for current and past business decisions visualized in graphical form. The problem in this study is modeled in the Big Data architecture with the aim of comparing the trend of the spread of Covid-19 related to process regulation. Based on the distribution map data and the regulation of health protocol rules with various online data sources, structured and unstructured using Business Intelligence (BI) cleaning data, three patterns of spread of the corona virus were found, High Cases, Medium Cases and Low Cases from 34 provinces throughout Indonesia. West Java Province became the first order of the highest cases during May 2021 with an average case of 21% followed by DKI Jakarta 14%.